Strategic alliances: enhancing tourism industry in Melaka / Abdul Rahman Darus, Nor Hamiza Mohd Noor and Hasnah Idris (Faculty of Business and Management, 2007)
Melaka is a well-known tourist destination in the Asian region in-line with the theme "Visit Historic Melaka Means Visit Malaysia". In 2006 the average tourists' stay in Melaka were 1.89 days(Malacca Tourism Board Promotion 2006), it is far less than the targeted by the stakeholders 3 days and more. The exploratOlY research was carried out to obtain information about the tourist length of stay in Melaka .The length of stay is about 1.89 days, whereby at the national level, the rate is 6 days. The research is to enhance strategic alliances among the stakeholders to collaborative each other to make the tourists stay longer in Melaka. The Strategic Alliances is to meet new relationship in terms ofjoint venture, partnership, licensing and others. The importance ofrelationship quality is to optimize stakeholders and tourist satisfaction, revenues and business efficiency. This research is to utilize an appropriate methodology to measure the relationship quality between the stakeholders and tourists. The researcher helped the stakeholders will identifying the factors that contribute to the relationship quality and its importance in aligning the strategic alliances. The researcher also identified the strength and weaknesses of each factors and came out with recommendations such as enhancing the efforts to build up long term relationship quality amongst the stakeholders.